Determinants of Interest and Behavior Among Adolescents in Accessing Reproductive Health Services through Social Media Platforms: A Study of Health Students in Cirebon City: Determinan Minat dan Perilaku Remaja dalam Mengakses Layanan Kesehatan Reproduksi melalui Platform Media Sosial: Studi pada Mahasiswa Kesehatan di Kota Cirebon - Hendriyanti Lestari, Sri; Fitriana, Nana; Rosidah, Rosidah; Meristika Rachman, Silvia; Rachmawati, Laily (MPI Press, 2025)
Introduction: Adolescent reproductive health (ARH) remains a critical global issue, with social media serving as a primary yet complex information channel for youth. Understanding how health students, as future professionals, engage with these platforms for ARH is essential. Objectives: This study aimed to analyze the determinants of interest and behavior among health students in Cirebon City in accessing ARH services through social media platforms. Method: A cross-sectional study was conducted from January to March 2025, involving 150 health students from three institutions selected via proportionate stratified random sampling. Data were analyzed using descriptive statistics and bivariate tests (t-test, ANOVA, Pearson correlation, Chi-Square). Result: The results revealed that knowledge (r = 0.612) and trust (r = 0.489) were strongly and positively correlated with both interest and behavior (p < 0.001). Gender (p = 0.015) and academic program (p = 0.016) were also significantly associated with interest. A notable gap was identified between students' high interest and their more moderate actual service-seeking behavior. Conclution: To effectively leverage social media for ARH, interventions must cultivate digital health literacy and trust. Addressing the practical barriers that create an